International travelers with infectious diseases determined by pathology results, Centers for Disease Control and Prevention — United States, 1995–2015. Issue 19 (September 2017) - Angelo, Kristina M.; Barbre, Kira; Shieh, Wun-Ju; Kozarsky, Phyllis E.; Blau, Dianna M.; Sotir, Mark J.; Zaki, Sherif R.
Abstract: Background: The failure to consider travel-related diagnoses, the lack of diagnostic capacity for specialized laboratory testing, and the declining number of autopsies may affect the diagnosis and management of travel-related infections. Pre- and post-mortem pathology can help determine causes of illness and death in international travelers. Methods: We conducted a retrospective review of biopsy and autopsy specimens sent to the Infectious Diseases Pathology Branch laboratory (IDPBL) at the Centers for Disease Control and Prevention (CDC) for diagnostic testing from 1995 through 2015. Cases were included if the specimen submitted for diagnosis was from a traveler with prior international travel during the disease incubation period and the cause of illness or death was unknown at the time of specimen submission. Results: Twenty-one travelers, six (29%) with biopsy specimens and 15 (71%) with autopsy specimens, met the inclusion criteria. Among the 15 travelers who underwent autopsies, the most common diagnoses were protozoal infections (7 travelers; 47%), including five malaria cases, followed by viral infections (6 travelers; 40%). Conclusions: Biopsy or autopsy specimens can assist in diagnosing infectious diseases in travelers, especially from pathogens not endemic in the U.S. CDC's IDPBL provides a useful resource for clinicians considering infectious diseases in returned travelers.